NGHIÊN CỨU SỬ DỤNG BENTONIT BÌNH THUẬN BIẾN TÍNH LÀM XÚC TÁC CHO PHẢN ỨNG HECK GIỮA IOTBENZEN VÀ STYREN - Sơn Nam, Phan Thanh; Hồng Hương, Bùi Thị; Tuệ, Đặng Đức; Thanh Thảo, Trần Thị (Vietnam Journal of Chemistry, 2012)
Modified Binh Thuan bentonite catalyst was prepared by exchanging with aqueous solution of PdCl2, giving a catalyst loading of 0.14 mmol of Pd/g (AAS). The Pd2+ - exchanged bentonite effectively catalyzed the Heck carbon-carbon coupling reaction between iodobenzene and styrene. The reaction was performed using 0.5 mol% catalyst at 120 oC in dimethylformamide (DMF) in the presence of Na2CO3 as a base, affording the coupling products in excellent conversions (GC). It was also observed that the catalyst could be facilely separated from the reaction mixture and could be reused in subsequent reaction without significant degradation in activity